Kinematics of bell-spigot joints in vitrified clay pipelines under differential ground movement. (September 2019) - Qin, Xiaogang; Ni, Pengpeng
Abstract: A simplified three-dimensional finite element model of bell-spigot joints in vitrified clay (VC) pipelines is introduced, which allows the simulation of rotation, axial translation, and moment-release behavior at joints. Then the kinematic responses of VC pipelines subjected to ground subsidence with two different joint-ground dislocation configurations are studied. Results show that axial extension and contraction can occur in the adjacent joints of the rotated pipe segment. The maximum kinematic response occurs when the fault offset passes through the midpoint of a pipe segment with a relatively shallow burial depth. Based on the numerical results, an empirical kinematic solution considering the rigid body rotation and dimensions of the pipe segment is proposed, which can provide a straightforward estimation on the axial translation of bell-spigot jointed VC pipelines subject to ground subsidence.